L’apport de l’étude d’un corpus de cartes anciennes dans la connaissance des jardins : l’exemple du château de Maisons - Marie Morillon (Les Cahiers de l'École du Louvre)
Old maps and plans provide a wealth of information on architecture and gardens. Within the framework of a case study, which in this case concerns the gardens of the Château de Maisons, laid out in the mid-seventeenth century by François Mansart for René de Longueil, two lines of research were developed. The first was to draw up an inventory of the maps representing the landscaping of Maisons. It involved the study of several collections, kept in libraries and archives. The corpus obtained calls for several typologies of maps, with diverse issues. The second concerned the analysis of this corpus and of cartographic representation. Maps are a language that must be learned to highlight the structural evolutions of the gardens of Maisons.